One step synthesis of fluorescent carbon dots through pyrolysis of N-hydroxysuccinimide. Issue 4 (2nd December 2014) - Stan, C. S.; Albu, C.; Coroaba, A.; Popa, M.; Sutiman, D.
Abstract : Fluorescent carbon dots were prepared via a simple and straightforward one-step pyrolytic process using N -hydroxysuccinimide. Abstract : Fluorescent carbon dots were prepared via a simple and straightforward one-step pyrolytic process using N -hydroxysuccinimide. The prepared C-dots present remarkable photoluminescence with blue to green shifting emission and absolute quantum yields varying from 14 to 31% as a function of the excitation wavelength and selected dispersion media. Interestingly, up-conversion from NIR to the visible range was not only instrumentally recorded but even visually observable. Further, the composition and morphology of the prepared C-dots were studied using XPS, FT-IR, Raman, P-XRD, DLS and AFM as investigation methods. Since the majority of C-dot studies are biased towards fluorescent labeling in cellular imaging, their photoluminescence properties, physicochemical stability and ease of fabrication are expected to play a key role in applications ranging from sensors to efficient solar energy conversion or high performance optoelectronic devices.